Steady MHD boundary free convective heat and mass transfer flow over an inclined porous plate with variable suction and Soret effect in presence of hall current (Bangladesh Journal of Scientific and Industrial Research, 2015)
In this paper an attempt is made to study the Hall effects on the steady MHD free convective flow of an incompressible fluid, heat and mass transfer over an inclined porous plate with variable suction and Soret effect. The flow is considered under the influence of a uniform magnetic field. The magnetic field is applied normally to the flow. The governing partial differential equations are transformed into ordinary differential equations by using similarity transformation and stretching variable. The governing momentum boundary layer, thermal boundary layer and concentration boundary layer equations with the boundary conditions are transformed into a system of first order ordinary differential equations which are then solved numerically by using Runge-Kutta fourth-fifth order method along with shooting iteration technique. The effects of the flow parameters on the primary and secondary velocities, temperature and species concentration are computed, discussed and have been graphically represented in figures for various value of different parameters.The results presented graphically illustrate that primary velocity field decrease due to increasing of magnetic parameter, permeability parameter, Grashof number, Dufour number and suction parameter and reverse trend arises for the increasing values of Hall parameter and modified Grashof number. The secondary velocity increase for increasing values of magnetic parameter, Hall parameter and permeability parameter and reverse trend arise for Grashof number, modified Grashof number and Suction parameter. The temperature field increases for the increasing values of magnetic parameter, Suction parameter, Soret number,Grashof number and modified Grashof number, Prandtl number whereas there is no effects of permeability parameter on temperature profile. Again, concentration profile decreases for increasing the values of magnetic parameter, Grashof number, modified Grashof number, and Schmidt number and the effect of the remaining entering parameter, the concentration increases up to certain interval of eta and then decreased. Alsothe numerical solutions for the skin friction [f (0)], secondary skin friction [g0(0)] and local Sherwood number [-?(0)] have been shown in Table I. DOI: http://dx.doi.org/10.3329/bjsir.v49i3.22129 Bangladesh J. Sci. Ind. Res. 49(3), 155-164, 2014